UMPSA and UMW collaboration planted 2,000 Mangrove trees in Cherating - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2023)
CHERATING, 25 November 2023 – The collaboration between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and UMW recently planted 2,000 mangrove trees in Cherating with the target of planting 300,000 mangrove trees by 2023.